E-Learning: Local Perspective - Afsar, Sardar Sohail (Journal of Postgraduate Medical Institute, 2011)
It is a privilege to see editorial on a very important subject of modern era by such a prestigious figure. At this point in time, so much revolution is happening on ways of getting and delivering knowledge in almost all fields of life including medical profession. It is very important and encour aging s ign to s e e tha t in our environment, people are working to change the mind set of people and make them aware of ways and methods by which learning opportunities increases by many folds and economy. In this modern era of science and technology one has to go hand in hand with it so as to get maximum advantage